(untitled) (American Journal of Interdisciplinary Research and Innovation, 2023)
Research is essential to the improved practice of a profession and is indispensable in completing a program of study. However, the difficulty and challenges in conducting research are remarkable among business education students. The study examines the research self-efficacy among business education students employing a cross-sectional survey design. Further, the study looks into the difference in the research self-efficacy of business education regarding gender and program of study. In addition, the relationship between research self-efficacy among business education students and their gender and program of study is also evaluated. A structured questionnaire was administered to 149 business education students, and it was revealed that the research self-efficacy of business education students is somewhat confident; however, there is no significant difference in the research self-efficacy in terms of gender and program of study and no significant relationship between gender and program of study and their research self-efficacy. The study suggests integrating research into coursework to promote their confidence to conduct research. Moreover, a recommendation is to conduct a follow-up study employing a longitudinal research design per program and to consider other variables that would strengthen a positive research experience among the student. This study will be a basis for disseminating information that promotes confidence among students to enhance their research productivity.